2014
DOI: 10.1021/ol500738g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorous-Assisted Chemoenzymatic Synthesis of Heparan Sulfate Oligosaccharides

Abstract: The chemoenzymatic synthesis of heparan sulfate tetrasaccharide (1) and hexasaccharide (2) with a fluorous tag attached at the reducing end is reported. The fluorous tert-butyl dicarbonate (FBoc) tag did not interfere with enzymatic recognition for both elongation and specific sulfation, and flash purification was performed by standard fluorous solid-phase extraction (FSPE). Based on an FBoc attached disaccharide as acceptor, a series of partial N-sulfated, 6-O-sulfated heparan sulfate oligosaccharides were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
(47 reference statements)
0
46
0
Order By: Relevance
“…Protocols for synthesizing HS oligosaccharide on the basis of chemoenzymatic reactions have been established . Comprehensive reviews in the area have been published .…”
Section: Synthetic Gagsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protocols for synthesizing HS oligosaccharide on the basis of chemoenzymatic reactions have been established . Comprehensive reviews in the area have been published .…”
Section: Synthetic Gagsmentioning
confidence: 99%
“…Another example is the 2‐ O ‐sulfated GlcA‐containing HS hexasaccharides recently produced by Hsieh and co‐workers . As seen for the modular‐based synthesis of HS oligosaccharides, fluorous tag can be also fruitfully used in chemoenzymatic‐based synthesis of HS tetrasaccharide and hexasaccharide . It has been reported that this tag besides facilitating purification steps via FSPE does not interfere with any enzyme involved in the elongation and further modification of HS chains …”
Section: Synthetic Gagsmentioning
confidence: 99%
“…In glycosaminoglycanomics, for example, GAG‐like molecules (mostly oligosaccharides of well‐defined structures and sizes) have been successfully synthesized . GAG synthesis can be accomplished either by chemoenzymatic routes or based on modular assembly of pre‐synthesized building blocks . Module‐based synthesis is sometimes used in conjunction with additional chemical and/or enzymatic steps to increase yield and diversity of sulfation patterns .…”
Section: Common Synthetic Routes and Gag Oligosaccharide Librariesmentioning
confidence: 99%
“…Protocols to synthesize HS oligosaccharide on the bases of chemoenzymatic reactions have been established . Comprehensive reviews in the area have been published .…”
Section: Common Synthetic Routes and Gag Oligosaccharide Librariesmentioning
confidence: 99%
See 1 more Smart Citation